Teaching Profession - Dasopang, Tepiani (Education Achievement: Journal of Science and Research, 2024)
The purpose of this writing is to discuss the concept of the teaching profession. In the context of teaching, planning can be interpreted as the process of compiling lesson materials, using teaching media, using approaches, teaching methods, and assessments in a time allocation that will be carried out at a certain time to achieve predetermined goals. Professional Competence describes the abilities that must be possessed by someone who holds a position as a teacher, meaning that it can show that it is a characteristic of his professionalism. In addition, teachers must also have competencies that reflect a steady, stable, mature, wise personality and be a role model for their students. From the explanation above, teachers are often considered as figures who have ideal personalities. Because teachers are also considered role models to be imitated, therefore they must have the competencies mentioned above.